- Moderasi Komisaris Independen Terhadap Faktor-Faktor Penentu Tax Avoidance (Studi Empiris: Perusahaan Sektor Pertambangan yang Terdaftar di BEI Pada Tahun 2018-2022) - TRIA SEPTIALA, RIVE; Diah PA, Enggar; Wiralestari, Wiralestari (Jurnal Akuntansi & Keuangan Unja, 2024)
This study aims to determine the effect of Capital Intensity, Inventory intensity, Corporate risk, Leverage and Profitability on Tax avoidance in Mining Sector Companies Listed on the IDX for the 2018-2022 period. The population in this study were 63 Mining Companies on the Indonesia Stock Exchange Based on Sub-Industry. The sample in this study used random sampling that published reports within a period of 5 years with a total sample of 19 companies. This research method uses a quantitative method. This study uses secondary data obtained through data on idx.com, yahoo.finance.com and the company's respective websites. This study uses multiple linear analysis using SPSS 26 software. The results of the study indicate that Capital Intensity, Inventory intensity, Corporate risk and Profitability have an effect on Tax avoidance in Mining Sector Companies Listed on the IDX for the 2018-2022 period, only the Leverage variable does not affect Tax avoidance.